2015
DOI: 10.1016/j.devcel.2014.12.013
|View full text |Cite
|
Sign up to set email alerts
|

A Dicer-miR-107 Interaction Regulates Biogenesis of Specific miRNAs Crucial for Neurogenesis

Abstract: Dicer controls the biogenesis of microRNAs (miRNAs) and is essential for neurogenesis. Recent reports show that the levels and substrate selectivity of DICER result in the preferential biogenesis of specific miRNAs in vitro. However, how dicer expression levels and miRNA biogenesis are regulated in vivo and how this affects neurogenesis is incompletely understood. Here we show that during zebrafish hindbrain development dicer expression levels are controlled by miR-107 to tune the biogenesis of specific miRNAs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
38
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 52 publications
0
38
0
Order By: Relevance
“…This results in global downregulation of mature miRNAs, with miR-9 showing the strongest response to increased miR-107 activity. In situ hybridization studies have further revealed that the localization of miR-107 and Dicer is mutually exclusive along the hindbrain ventricular zone, thereby determining the border between the progenitor pool and differentiated neurons (Ristori et al, 2015).…”
Section: Neurogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…This results in global downregulation of mature miRNAs, with miR-9 showing the strongest response to increased miR-107 activity. In situ hybridization studies have further revealed that the localization of miR-107 and Dicer is mutually exclusive along the hindbrain ventricular zone, thereby determining the border between the progenitor pool and differentiated neurons (Ristori et al, 2015).…”
Section: Neurogenesismentioning
confidence: 99%
“…Furthermore, TLX negatively regulates miR-9 expression levels, pointing to sophisticated feedback mechanisms that precisely control the balance between neural stem cell renewal and differentiation . To further complicate matters, miR-9 levels are also regulated by another miRNA, miR-107 (Ristori et al, 2015). Indeed, in the zebrafish MHB, miR-107 directly inhibits expression of the miRNA processing factor Dicer.…”
Section: Neurogenesismentioning
confidence: 99%
“…So, we only focus on the latest research progress in the role of miRNA in neurogenesis. Recently, Ristori et al [132] show that miR-107 modulates the expression of Dicer and also interacts with Dicer during zebrafish hindbrain development. The miR-107-dicer interaction is indispensable for the specific accumulation of miR-9, which is crucial to neurogenesis [131,132].…”
Section: Ncrnas In Embryonic Neurogenesismentioning
confidence: 98%
“…Recently, Ristori et al [132] show that miR-107 modulates the expression of Dicer and also interacts with Dicer during zebrafish hindbrain development. The miR-107-dicer interaction is indispensable for the specific accumulation of miR-9, which is crucial to neurogenesis [131,132]. Furthermore, miRNAs can also interplay with other epigenetic regulators and play a comprehensive role in regulating neurogenesis [133].…”
Section: Ncrnas In Embryonic Neurogenesismentioning
confidence: 98%
“…Here we describe a neurosphere-forming assay to demonstrate the role of miR-107 during zebrafish neurogenesis 11 . The protocol enables: 1) the collection of adult neural stem/progenitor cells either from zebrafish whole brain or from several dissected brain regions such as the telencephalon, the tectum, and the cerebellum; 2) the generation of floating and self-renewing neurospheres from adult neural stem/progenitor cells; 3) the down- and up-regulation of the expression of coding genes or small non-coding RNAs 11 in neurospheres, in order to investigate their roles in the proliferation and differentiation of neural stem/progenitor cells.…”
Section: Introductionmentioning
confidence: 99%